2020
DOI: 10.1016/j.pediatrneurol.2020.08.016
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 and Pediatric Neurology Practice in a Developing Country

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 10 publications
(8 reference statements)
0
5
0
Order By: Relevance
“…Pediatrics : It has been indicated that neurological diseases of pediatrics such as Guillain‐Barre syndrome, multiple sclerosis, infantile spasms, acute disseminated encephalomyelitis, and febrile seizures are associated with COVID‐19. 110 , 111 Recent reports described emerging pediatric cases diagnosed with MIS‐C with an unexpectedly high incidence (34%) of neurological involvement. 112 …”
Section: Methodsmentioning
confidence: 99%
“…Pediatrics : It has been indicated that neurological diseases of pediatrics such as Guillain‐Barre syndrome, multiple sclerosis, infantile spasms, acute disseminated encephalomyelitis, and febrile seizures are associated with COVID‐19. 110 , 111 Recent reports described emerging pediatric cases diagnosed with MIS‐C with an unexpectedly high incidence (34%) of neurological involvement. 112 …”
Section: Methodsmentioning
confidence: 99%
“…The pandemic subsequently engulfed more than 200 countries with more than 165 million people being affected and around three million deaths [ 1 ]. COVID-19 pandemic along with the inevitable lockdowns have had a significant impact on lifestyle behaviors and patient-care worldwide [ 2 ]. With new waves of COVID-19 and the re-imposition of lockdowns in different parts of the world, it becomes imperative to study the true impact of initial lockdown in the early phase of the COVID-19 pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…While participants continued their occupations, they mentioned difficulties encountered, need for new developments and alternative communication routes over time. Though living in three separate regions of the world’s geography, Dr. Pavlakis and Dr. Grupta and colleagues noted the same problems encountered by Turkish pediatric neurologists in their letters from a similar period ( 8 , 19 , 20 ). Apart from the load brought by the pandemic, it is known that health employees shared concerns about attempting to reorganize the disrupted routine health services caused by the pandemic, with variations according to country.…”
Section: Discussionmentioning
confidence: 91%
“…In developed or developing countries, pediatric neurology practice encountered situations like increased telemedicine implementations, changes to treatment regimes, and difficulty accessing epilepsy surgery-diet clinics ( 7 , 8 ). Though health authorities or institutions sometimes offered solutions to these problems, the extremely fast progress in this period pushed pediatric neurologists to find individual solutions.…”
Section: Introductionmentioning
confidence: 99%